2006
DOI: 10.1063/1.2158700
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of labelled single nitrogen vacancy centers in diamond using N15

Abstract: Nitrogen-vacancy (NV -) color centers in diamond were created by implantation of 7 keV 15 N (I = ½) ions into type IIa diamond. Optically detected magnetic resonance was employed to measure the hyperfine coupling of the NV -centers. The hyperfine spectrum from 15 NV -arising from implanted 15 N can be distinguished from 14 NVcenters created by native 14 N (I = 1) sites. Analysis indicates 1 in 40 implanted 15 N atoms give rise to an optically observable 15 NV -center. This report ultimately demonstrates a mech… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
201
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(206 citation statements)
references
References 15 publications
5
201
0
Order By: Relevance
“…The highest conversion efficiencies estimated here are similar to those obtained through pure nitrogen implantation at a similar energy range. 22,28 Higher conversion efficiencies, up to 50%, have only been obtained with MeV nitrogen implantation energies 25 or with nitrogen and carbon co-implantation. 24 Next, we discuss the optical spectral linewidths for NV centers created using this method.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The highest conversion efficiencies estimated here are similar to those obtained through pure nitrogen implantation at a similar energy range. 22,28 Higher conversion efficiencies, up to 50%, have only been obtained with MeV nitrogen implantation energies 25 or with nitrogen and carbon co-implantation. 24 Next, we discuss the optical spectral linewidths for NV centers created using this method.…”
mentioning
confidence: 99%
“…[18][19][20][21] The most commonly used technique to create NV centers near a surface is implantation of nitrogen ions followed by annealing at 900 C. [22][23][24] Rabeau et al reported a creation yield of 2.5% for the optically detectable NV À centers per implanted nitrogen (N) ion. 22 Pezzagna et al investigated a wide range of nitrogen implantation energies from 5 keV to 18 MeV and gave the dependence of the NV yield on the ion energies. 25 Naydenov et al determined that co-implantation of carbon and nitrogen ions increases the NV À conversion efficiency to up to 50%.…”
mentioning
confidence: 99%
“…to the nitrogen nuclear spin ( [25] and is inhomogeneously broadened by the 13 C nuclear spin bath [23,26]. Other minor broadening effects are impurity electron spins or fluctuating electric or magnetic fields.…”
mentioning
confidence: 99%
“…The last two samples were produced by a high purity CVD procedure with an initial nitrogen concentration of ∼ 2 × 10 14 N/cm 3 and an NV concentration that was below the detection limit. These two samples then underwent a nitrogen implantation process (Innovion) [20,[23][24][25][26], at an energy of 20 keV and doses of 2 × 10 11 and 2 × 10 12 N/cm 2 , followed by standard annealing (Across International TF1400): 8 hours, temperature 800 o C, vacuum ∼ 7.5 × 10 −7 Torr (hereafter -we refer to these two samples as nitrogenimplanted CVD). The maximum depth of the nitrogen layer created by the implantation is ∼ 100 nm, limited by ion channeling [26].…”
mentioning
confidence: 99%